2018
DOI: 10.1002/syn.22080
|View full text |Cite
|
Sign up to set email alerts
|

In vivo voltammetric evidence that locus coeruleus activation predominantly releases norepinephrine in the infralimbic cortex: Effect of acute ethanol

Abstract: Using fast‐scan cyclic voltammetry paired with pharmacology, the authors show that infralimbic catecholamine release following locus coeruleus stimulation is noradrenergic, but not dopaminergic, and not affected by acute ethanol. With previous work, these data suggest differential effects of ethanol on prefrontal norepinephrine and dopamine, a region important in addiction‐related pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Ethanol inhibition of BG activation was dose-dependent, reaching almost complete inhibition at 1.5 g/kg (i.p.). This ethanol dosage is within the range used for acute ethanol exposure studies of rodents 23,28,37 , and caused temporary ataxic motor coordination as discussed below, but did not impair their ability to walk on the treadmill while head restrained (Fig. 1d).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Ethanol inhibition of BG activation was dose-dependent, reaching almost complete inhibition at 1.5 g/kg (i.p.). This ethanol dosage is within the range used for acute ethanol exposure studies of rodents 23,28,37 , and caused temporary ataxic motor coordination as discussed below, but did not impair their ability to walk on the treadmill while head restrained (Fig. 1d).…”
Section: Resultsmentioning
confidence: 88%
“…Fastscan cyclic voltammetry is an electrochemical approach to monitor neurotransmitter dynamics at subsecond time resolution 65 ; however, despite considerable recent progress it can be challenging to distinguish between the detection of dopamine and NE 66 . Both, microdialysis and fast-scan cyclic voltammetry experiments revealed that depending on the brain region and experimental paradigm acute ethanol can lower, raise or leave extracellular NE concentration unchanged [26][27][28]37 .…”
Section: Discussionmentioning
confidence: 99%
“…Fox et al, 2016;Deal et al, 2019), our results for the first time demonstrate the possibility to measure real-time NE efflux in the BLA. Based on pharmacological characterizations, we ruled out the involvement of DA efflux in the signal measured in naïve rats as previously reported for the prefrontal cortex and bed nucleus of the stria terminals (Park et al, 2011;Fox et al, 2016;Deal et al, 2019). As expected, the electrically-evoked NE release was frequency-dependent, while the average maximum concentrations were ∼2-3 fold lower than concentrations in the prefrontal cortex (Deal et al, 2019).…”
Section: Discussionmentioning
confidence: 58%
“…The locus coeruleus (LC) is a key brainstem nucleus involved in stress and arousal (Szabadi, 2013;Naegeli et al, 2018;Daviu et al, 2019). This pontine structure is the primary source of noradrenergic projections in the central nervous system which target many regions throughout the brain, such as the amygdala, thalamus, hypothalamus, and prefrontal cortex, associating the LC with myriad behavioral, motor, and sensory processes (Samuels and Szabadi, 2008;Deal et al, 2019). In particular, the projection from the LC to the basolateral amygdala (BLA) has been proposed as an important pathway in anxiety-related processes and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…The LC is a catecholamine nucleus and NE is its primary neurotransmitter [23]. With extensive projections throughout the central nervous system [24], this brainstem region has a major role in stress-related behaviors [25], and is involved in the shaping of alcohol-drinking behaviors [21,26]. It is known that aversive states induce LC activation, including ethanol in doses that support CTA [27][28][29][30].…”
Section: Hindbrain Regionsmentioning
confidence: 99%